Making Services Work : Indicators, Assessments, and Benchmarking of the Quality and Governance of Public Service Delivery in the Human Development Sectors - Fiszbein, Ariel (2012)
Improving governance is central to improving results in human development. It is clear that money is not enough: improved outcomes from service delivery require better governance, including mechanisms for holding service providers accountable and appropriate incentives for performance. There is therefore a growing demand for indicators to measure how and whether these processes work, and how they affect health and education results. This paper makes the case for measuring governance policies and performance, and the quality of service delivery in health and education. It develops a framework for selecting and measuring a set of indicators and proposes options, drawing from new and innovative measurement tools and approaches. The paper proposes the adoption of a more systematic approach that will both facilitate the work of health and education policymakers and allow for cross-country comparisons and benchmarking.